Methods of predicting the probability of task man-operator on the criterion limit of time - Поліщук, С.Т. (Proceedings of National Aviation University (archive), 2009)
The probabilistic characteristic for estimation of human-operator cybernetic performance capabilities with the help of time limit criteria is determined. The method for used of this characteristic during of pilot testing on the simulator is proposed.